Membangun Masyarakat Sehat Dan Lingkungan Bersih: Pelaksanaan Kkn Tematik Universitas Dehasen Periode 6 Di Kelurahan Betungan Rt 28 Rw 02 - Jeki Putra Jaya; Sari Putri Dewi; Cici Hidayatullah; Anwar Fuadi Lubis; Triyogi Prabowo; Ferawati Royani; Feby Elra Perdima; Asnawati Asnawati (Jurnal Karya Nyata Pengabdian, 2026)
This community service activity was conducted in RT 28 RW 02 Betungan Subdistrict and Sumber Jaya Betungan to address environmental, health, literacy, and social cohesion issues within the community. The main problems identified included limited green open spaces, low awareness of waste management, restricted access to reading materials, and a lack of collective health activities. The solutions implemented focused on community empowerment programs, such as planting medicinal plants, organizing group exercise activities, providing waste bins, establishing reading corners, installing educational signboards, conducting environmental cleanup activities, and developing a community garden. The methods applied consisted of field observation, participatory planning, program implementation, and joint evaluation with community members. The results indicate increased public awareness of environmental cleanliness and healthy lifestyles, improved access to literacy facilities, and stronger community participation and social solidarity.Therefore, this community service program effectively contributed to problemsolving efforts and supported the sustainability of community-based environmental development.